Maximizing marketing impact: examining video content through analytics and consumer behaviour - Penkova, Oksana; Sogorin, Andriy; Kitchenko, Olena; Klimovych, Olha; Tesak, Oleksandra (AG Editor, 2025)
Introduction: the article examines the impact of video content on the effectiveness of marketing strategies with a focus on analytical interpretation of audience behavioral reactions. The purpose of the study is to analyze the potential of marketing campaigns in the context of adaptation to changes in media consumption. Method: the study was based on the analysis of secondary empirical data obtained from authoritative analytical reports covering current trends in video marketing and digital consumer engagement. The methods used are quantitative content analysis, thematic classification, and discursive interpretation. Results: it is found that video content demonstrates a high level of strategic importance - 95 % of marketers recognize it as a key tool for influencing the target audience. The main types of barriers to video implementation are identified: lack of time and technical complexity. It is established that video helps to increase brand trust, forms emotional contact with the consumer, and provides an opportunity to accurately measure audience reactions through digital metrics (watch time, CTR, engagement rate). It is shown that cultural relevance, professional visual quality, and artificial intelligence support are key factors in the effectiveness of video on social media. Conclusions: the article emphasizes the need for a comprehensive integration of video content into strategic planning, including the development of intra-team competencies, analytical reporting, and automated video performance evaluation systems. Prospects for the study are to form adaptive models of video strategy focused on changing consumer behavioral patterns and digital transformation of marketing communications in various sectors.
Keywords: video content; marketing strategy; behavioral analytics; communication effectiveness; video marketing; digital metrics; strategic integration; advertising impact